Pediatric pulmonary arterial hypertension: global epidemiology and disease burden during the period 1990 to 2021 - Chen, Ying; Zhang, Rongguo; Zheng, Yongxiao; Li, Chenghong; Wang, Xiaobei; Wen, Zhongmei; Li, Fajiu (Frontiers in Cardiovascular Medicine, 2025)
ObjectivesPediatric pulmonary arterial hypertension (PAH) is a severe and potentially fatal disease; however, the global epidemiological burden of pediatric PAH has not been comprehensively elucidated.Study designThe Global Burden of Diseases Study 2021 has incorporated PAH for the first time. This study analyzed the incidence, prevalence, mortality, and disability-adjusted life years (DALYs) associated with pediatric PAH from 1990 to 2021.ResultsGlobally, the age-standardized prevalence rate (ASPR) of pediatric PAH in children aged 0–14 years showed a relatively stable, from 0.44 per 100,000 in 1990 to 0.43 per 100,000 in 2021. Females exhibited higher age-standardized incidence rates (ASIR) and ASPR compared to males. The ASIR of pediatric PAH increased modestly, with an average annual growth of 0.12%. Children aged 10–14 years had the highest prevalence, with rates of 0.66 per 100,000 in 1990 and 0.65 per 100,000 in 2021. In contrast, newborns aged 0–6 days experienced the highest mortality rates (34.16 and 13.67 per 100,000) and DALYs rates (3,073.56 and 1,229.88 per 100,000) during the same period. Countries with high-middle SDI levels had the highest ASPR, while high-SDI countries reported the lowest age-standardized mortality rate and age-standardized disability rate.ConclusionsGlobally, prevalence, mortality, and DALYs of pediatric PAH show a declining trend from 1990 to 2021. Females exhibited higher incidence and prevalence rate but lower mortality and DALYs. 10–14 years had the highest prevalence, whereas high PAH-related mortality in neonates remains a critical concern. Tailored health policies for PAH management are needed.